2003
DOI: 10.3354/meps261269
|View full text |Cite
|
Sign up to set email alerts
|

Deep-diving by narwhals Monodon monoceros: differences in foraging behavior between wintering areas?

Abstract: Variation in resource selection among sub-populations may elucidate differences in fitness and life history strategies. Specifically for top marine predators, differences in movements and behavior may result from responses to variation in a patchy, dynamic environment. Satellite-linked time-depth recorders (SLTDRs) were used to examine differences in narwhal Monodon monoceros diving behavior and habitat selection among 3 sub-populations in Canada and West Greenland (n = 16 individuals). The number of dives to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
79
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 101 publications
(85 citation statements)
references
References 23 publications
6
79
0
Order By: Relevance
“…Studies investigating dive behavior in narwhal sexes have been limited by sample size and perhaps, as a result, have documented conflicting results. It has been shown that female narwhals have significantly lower dive rates than males (Heide-Jørgensen and Dietz 1995) and they typically make dives ,400 m (Laidre et al 2004b), but another study reported no difference in diving performance between female narwhals and their male counterparts (Laidre et al 2003). Further evidence is required to support differences in dive behavior between males and females, but given the sexual size dimorphism (Garde et al 2007), males are likely capable of making deeper dives and therefore capable of foraging in the benthos even in deep waters.…”
Section: Values and The Highest Dmentioning
confidence: 99%
“…Studies investigating dive behavior in narwhal sexes have been limited by sample size and perhaps, as a result, have documented conflicting results. It has been shown that female narwhals have significantly lower dive rates than males (Heide-Jørgensen and Dietz 1995) and they typically make dives ,400 m (Laidre et al 2004b), but another study reported no difference in diving performance between female narwhals and their male counterparts (Laidre et al 2003). Further evidence is required to support differences in dive behavior between males and females, but given the sexual size dimorphism (Garde et al 2007), males are likely capable of making deeper dives and therefore capable of foraging in the benthos even in deep waters.…”
Section: Values and The Highest Dmentioning
confidence: 99%
“…Heide-Jørgensen and Bloch, 2002;Laidre et al, 2003;Schorr et al, 2014;Tyack et al 2006). Based on an allometric regression among odontocetes (Schreer and Kovacs, 1997), even a 6,000 kg killer whale would be capable of diving to 885 m and dive durations up to 43 min.…”
Section: Diving Behaviourmentioning
confidence: 99%
“…A variety of methods have been used, including satellite tracking (e.g. Laidre et al 2003), stomach content analysis (e.g. Spitz et al 2006), fecal analysis (e.g.…”
Section: Resale or Republication Not Permitted Without Written Consenmentioning
confidence: 99%